Reply to: Inaccuracy of pulse oximetry in darker-skinned patients is unchanged across 32 years. Issue 6 (23rd June 2022) - Crooks, Colin; West, Joe; Card, Tim; Shaw, Dominick; Simmonds, Mark; Fogarty, Andrew
We thank M.J. Tobin and A. Jubran for their interest in our data [1]. As they state, it is an extension of a body of work that they helped establish over 30 years ago. Inaccuracy of pulse oximetry measurements of oxygen saturation in darker-skinned individuals https://bit.ly/3rVzRpN